COMPARATIVE STUDY ON ANTIMICROBIAL ACTIVITY OF SEAWEEDS - C, Sasikala; D, Geetha Ramani (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Secondary metabolites from natural resources are a potential source of antimicrobial leads and drugs can exploited to combat antimicrobial resistance in microorganisms. Seaweeds are considered as a valuable source with a broad spectrum of biological activities. Hence, this study was undertaken to screen seaweeds from Mandapam coastal waters, East coast of India, for antimicrobial activity. Methods: Compounds were extracted using methanol from the seaweeds, namely, Halimeda gracilis, Caulerpa serrulata, Sargassum swartzii, Sargassum wightii, Jania rubens, Ulva lactuca, Ulva fasciata, Gracilaria corticata, Stoechospermum marginatum, Caulerpa scalpelliformis, Caulerpa taxifolia, Chaetomorpha crassa, Enteromorpha flexuosa, and Turbinaria ornate. The extracts were screened for their antimicrobial activity against selected bacterial and fungal pathogens. Results: In the present study, S. swartzii, J. rubens, and S. marginatum showed broad spectrum of antibacterial activity against all the test bacterial pathogens. Among these, the maximum activity was exhibited by S. swartzii against Enterococcus faecalis (27.00 ± 0.88) and Streptococcus pyogenes (23.00 ± 0.84), followed by J. rubens against E. faecalis (26.00 ± 0.56) and S. pyogenes (22.00 ± 0.75), and S. marginatum exhibited significant inhibition against Staphylococcus aureus (15.00 ± 0.22) and S. pyogenes (18.00 ± 1.16). Conclusion: These seaweeds with significant antibacterial activity will subjected to phytochemical screening to find out the potential active principle responsible for antimicrobial activity. It is followed by purification and characterization of the compounds for possible application in drug formulation, can take this to large-scale application in pharmaceutical industries.